Effects of Sarcosine (N-methylglycine) on NMDA (N-methyl-D-aspartate) Receptor Hypofunction Induced by MK801: In Vivo Calcium Imaging in the CA1 Region of the Dorsal Hippocampus - Yi-Tse Hsiao; Ching-Yuan Chang; Ting-Yen Lee; Wan-Ting Liao; Wen-Sung Lai; Fang-Chia Chang (Brain Sciences)
Background: Hypofunction of the glutamate system in the brain is one of the pathophysiological hypotheses for schizophrenia. Accumulating animal and clinical studies show that sarcosine (N-methylglycine), a glycine transporter-1 inhibitor, is effective in ameliorating the negative and cognitive symptoms of schizophrenia. The aims of the present study were to observe the effects of sarcosine on neuronal activity in the dorsal CA1 (dCA1) hippocampal neurons within an NMDA receptor hypofunction model induced by MK801. Methods: We applied in vivo calcium imaging to observe the dynamics of fluorescence from the dCA1 hippocampal neurons when the mice were exploring in an open field. Using this tool, we directly measured and compared neuronal properties between sarcosine-treated and untreated mice. At the same time, the physiological function of the neurons was also quantified by measuring their place fields. Results: Our data demonstrated that MK-801 (0.2 mg/kg) diminished the fluorescence intensity of dCA1 neurons that had been genetically modified with a calcium indicator. MK-801 also significantly increased the correlation coefficient between the fluorescence dynamics of pairs of cells, a feature that may be linked to the symptom of disorganization in human patients with schizophrenia. The spatial correlations of place fields in the mice were impaired by MK-801 as well. Injected sarcosine (500 mg or 1000 mg/kg) significantly alleviated the abovementioned abnormalities. Conclusions: Our data provide evidence to support the use of sarcosine to alleviate symptoms of schizophrenia, especially hippocampus-related functions.